Investigations of the identity of the true catalyst in three systems, including the development of catalyst poisoning methodology - Bayram, Ercan, author; Finke, Richard G., advisor; Chen, Eugene Y.-X., committee member; Prieto, Amy L., committee member; Bernstein, Elliot R., committee member; Dandy, David S., committee member (Colorado State University. Libraries, 2012)
Following brief reviews of the pertinent "who is the catalyst?" and "M4 (M= transition-metal) cluster catalysis" literature, the research presented herein is focused on the investigations of the true catalyst for three different catalytic systems. The studies include: (i) the investigation of the true catalyst for neat benzene hydrogenation beginning with commercially available [Ir(cod)Cl]2 (cod= 1,5-cyclooctadiene) at 22 °C and 40 psig initial H2 pressure; (ii) the investigation of the true catalyst for benzene hydrogenation beginning with commercially available [RhCp*Cl2]2 (Cp*= pentamethylcyclopentadienyl) at 100 °C and 50 atm (740 psig) initial H2 pressure; and (iii) the investigation of the true catalyst for cyclohexene hydrogenation beginning with the well-characterized, site isolated [Ir(C2H4)2]/zeolite-Y complex at 22 °C and 40 psig initial H2 pressure, studies done collaboratively with Professor Bruce C. Gates and his group at the University of California-Davis. All three investigations aimed at identifying the true catalyst were studied via an arsenal of complimentary techniques including kinetics, in operando and post-catalysis X-ray absorption fine structure (XAFS) spectroscopy, kinetic quantitative poisoning experiments, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and high-angle annular dark-field scanning electron microscopy (HAADF-STEM). The data obtained for each system presented herein provide compelling evidence that the proposed species in each chapter are the true catalyst of the given system, specifically (and respectively) for (i), (ii), and (iii) above Ir(0)n nanoparticles and aggregates, Rh4 sub-nanometer clusters, and atomically dispersed, mononuclear Ir1/zeolite Y catalysts. The results emphasize the need to use complimentary, multiple methods in order to correctly identify the true catalyst in such catalytic systems. The final study elucidates kinetic quantitative catalyst poisoning via two model catalysts: Rh(0)n nanoparticles and Rh4 clusters, providing detailed analyses of linear as well as non-linear kinetic quantitative poisoning plots. The resulting quantitative kinetic catalyst poisoning studies of Rh(0)n nanoparticles and Rh4 clusters led to estimates of the equivalents of poison bound, quantitative catalyst poisoning association constants, and the numbers of active sites for each catalyst.
Keywords: nanoparticle; cluster; catalysis